Strategi Indonesia dalam Mendorong Ekspor Industri Kreatif di Pasar Eropa - Halifa Haqqi & GPH. Dipokusumo (Universitas Slamet Riyadi, 2019)
Cultural and Creative Industries (CCIs) shows a significant increase, both globally and locally. The market for creative industries in Europe is also wide open. For Indonesia, the creative industry sector is also a leading sector. Unfortunately, many creative industry players do not understand the potential of this. Therefore, it is important to provide information about creative industry’s export potential to Europe. This research aims to find out how Indonesia's strategy in promoting the export of creative industries in the European market. This type of research is qualitative research with a qualitative descriptive approach. Primary and secondary data were analyzed by library study methods. The research results an overview of the export potential of creative industries in the European market along with the implementation of strategies that can be carried out to encourage creative industries export to the European market. The European market has great potential for creative industries from Indonesia. With adjustments to the European market, Indonesia's creative industries have the opportunity to be exported in Europe.Keywords : creative industry, Europe market, export.